Spatial gravity models for international trade: a panel analysis among OECD countries - Rodolfo Metulini (European Regional Science Association (ERSA), 2013)
The Gravity Model is the workhorse for empirical studies in International Economies and it is commonly used in explaining the trade flow between countries. Recently, several studies have showed the importance of taking into account the spatial effect. Spatial Econometric techniques meet this matter, proposing the specification of a set of models and estimators. We will make use of these Spatial Econometric techniques in order to estimate a Spatial Gravity of Trade for a 22-year-long panel of the OECD countries. The aim, therefore, is twofold: on one hand, we are going to use the newest Spatial Econometric techniques in a field where they aren't widely applicated. On the other hand, we provide an updated interpretation of the behaviour of the International Trade in an OECD context, taking into account potential spatial spillover effect due to the third country dependence, and the effects of the migratory phenomenon.
Keywords: 330; Spatial Econometrics; International Trade; Gravity Model; Spatial Spillover